SMART TECHNO PARENTING: PENDIDIKAN TEKNOLOGI PADA ANAK DI ERA VUCA - Sari Utami (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2022)
Children have to keep up with the ever-changing developments so as to make them always adapt according to their environment. The progress of an industry and technology is very important, especially during the Covid-19 pandemic that is hitting Indonesia today, because all the sophistication of something new based on technology is proof that in the future science and technology will become a very mandatory and important thing for children. . The era of VUCA (Volatility, Uncertainty, Complexity, Ambiguity) is known as the current world condition moves very quickly with all advances in technology and information. To be able to survive in the VUCA era, which is almost all digital, children must adapt for the sake of development in the ever-changing VUCA era. Therefore, as parents, we don't need to be afraid to go to new places, try new things or introduce new experiences to our children by providing proper preparation and support for parenting. This study uses a qualitative approach to the type of library research where researchers collect data from library sources. Data collection techniques were carried out through library data collection, from the results of several literatures that parents must understand existing technology to be wise parents in educating children in the current VUCA digital era. The latest technological breakthrough today, smart techno parenting exists as a form of education for children who are smart and able to keep up with the times by utilizing existing technology for the sake of education for their children. It becomes a bad activity that must be avoided if parents are not involved and do not understand a technology. In addition, parents must also have a smart parenting pattern that was previously only available through training. Technological advances in the current VUCA era, have made it easier for parents to obtain useful information that can be used to educate their children. Here are some useful tips for introducing technology education to children at an early age: Set time to learn about technology, the importance of creativity and innovation, use technology to provide cognitive stimulation in children, healthy and appropriate food intake will shape children's mindsets, Technology can be used to help children improve their motor skills.